2016
DOI: 10.1186/s12906-016-1487-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Salvadora persica L. and green tea anti-plaque effect: a randomized controlled crossover clinical trial

Abstract: BackgroundIn the author’s earlier in vitro investigation, a combination of 0.25 mg/ml green tea and 7.82 mg/ml Salvadora persica L. aqueous extracts was found to exhibit significant synergistic anti-bacterial and anti-adherence effects against primary plaque colonizers biofilm. A clinical trial was needed to support these preliminary in vitro results and to investigate its efficacy as a mouthwash in the control of dental plaque.MethodsA 24 h plaque re-growth, double-blinded, randomized crossover trial was carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…The studies were mostly performed in adult patients, up to 60 years old, whereas five studies were performed in children between the ages of 6 and 18 years [20–22, 27, 29, 36]. Some studies were of cross-over nature, with a washout period ranging from 2 to 10 days [28, 31, 35] and 2 to 8 weeks [9, 23, 29]. The inclusion and exclusion criteria of the eligible studies are listed in Additional file 4: Table S4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies were mostly performed in adult patients, up to 60 years old, whereas five studies were performed in children between the ages of 6 and 18 years [20–22, 27, 29, 36]. Some studies were of cross-over nature, with a washout period ranging from 2 to 10 days [28, 31, 35] and 2 to 8 weeks [9, 23, 29]. The inclusion and exclusion criteria of the eligible studies are listed in Additional file 4: Table S4.…”
Section: Resultsmentioning
confidence: 99%
“…Although the quality of studies varied due to the use of different criteria, none were excluded based on quality level. Seven papers were regarded as high quality [25, 31, 32, 34, 35, 41], while the remaining papers were of moderate quality [9, 20–24, 26–30, 36] . As for the risk of bias,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro results showed the antibacterial effect of the two‐component mouthwash against Streptococcus mitis , Streptococcus sanguinis , and Actinomyces viscosus , as well as an anti‐adhesive effect . The clinical trial found less plaque regrowth detected with a green tea and Salvadora persica mouthwash than with a chlorhexidine or placebo (distilled water) mouthwash . However, the effect on gingival parameters was not examined in this study.…”
Section: Natural Productsmentioning
confidence: 66%
“…There are several recently reported controlled clinical trials comparing green tea with chlorhexidine mouthwashes. Although these studies differ in design, such as the patient population, the treatment duration, and the green tea concentration, they all show that green tea reduces plaque and gingivitis scores . Additionally, these effects are comparable with those observed with chlorhexidine mouthwashes.…”
Section: Natural Productsmentioning
confidence: 96%